Single - incision totally extraperitoneal inguinal hernia repair - Medina, J. Pablo; Auvieux, Rodolfo; Cerutti, Roberto A.; Porto, Eduardo A.; Pirchi, Daniel E. (Revista Argentina de Cirugía, 2021)
Background: the laparoscopic treatment of inguinal hernia has gained greater acceptance, by virtue of the advantages already demonstrated by minimally invasive approach. For further improvement, the incorporation of new technical variants arises. Extraperitoneal inguinal hernia repair by single incision is a new option, not existing at present series of cases that confirm their feasibility and safety. Objective: to evaluate the feasibility and safety of this method in the treatment of reducible inguinal hernia. Materials and methods: in patients undergoing inguinal hernia repair by single incision laparoscopic surgery - TEP between August 2014 and August 2015; demographics, type and size of hernia, type and size of mesh, number of staples, operative time, hospital stay, and complications were analyzed. The intensity of postoperative pain using a visual analog scale, and degree of satisfaction was valued. Ultrasound of the periumbilical region (access site) and treated inguinocrural region, to assess the degree of associated morbidity and recurrence was performed. Results: forty three single-incision TEP hernia repairs were performed in 29 patients. They were bilateral in 14 patients (48.2%), 88.4% were men, with mean age 40 years (16-72). T2 and indirect hernias comprised 72% of cases. The average length of stay was 0.56 days (0.5-1.5). The average intensity of pain at 12 hours and the 7th postoperative day was 4.1 points (range 1 to 8). The average degree of satisfaction with the cosmetic result was 9.5 (range 8-10). No major complications were recorded, and 4 cases (9.3%) had minor complication. The average operative time was